ダイ14ジ ナンキョク チイキ カンソクタイ ナイリク チョウサ ガイヨウ 1973 1974 - 成瀬, 廉二; ナルセ, レンジ; NARUSE, Renji (国立極地研究所, 1975)
P(論文) The oversnow traverse party of the 14th Japanese Antarctic Research Expedition (1973-1974) conducted researches according to the " Glaciological Research Program in Mizuho Plateau-West Enderby Land" and made, some geophysical observations at Mizuho Plateau, East Antarctica. Four oversnow traverses were made from Syowa Station to Mizuho Camp (70°41.9'S, 44° 19. 9'E) in January, April, August and September-October in 1973, and one traverse from Syowa Station to the Yamato Mountains via Mizuho Camp, from 10 November 1973 to 2 February 1974. The traverse party to the Yamato Mountains consisted of two glaciologists, one meteorologist, one geomagnetist, one geodesist, one geologist, one medical doctor, one field assistant and two mechanics. The party carried out the following tasks : 1) Measurement of the ice sheet flow by the resurvey of the triangulation chain which was installed by the JARE-10, in 1969 along the parallel of 72° S; 2) Measurement of the ice thickness by a radio echo sounder; 3) Measurement of net accumulation with snow stakes; 4) Observation of katabatic wind and micrometeorological conditions by radio sondes and a sonic anemometer; 5) Surface meteorological observation, three times a day; 6) Measurement of drifting snow; 7) Continuous observation of geomagnetic field and its pulsations; 8) Observation of VLF emission; 9) Measurement of the inclination and declination of geomagnetism; 10) Measurement of gravity by the LaCoste gravity meter; 11) Measurement of elevation by a barometric altimeter; 12) Terrestrial survey of the Yamato Mountains; 13) Geological survey of the Yamato Mountains; 14) Observation of snowquake by a seismograph; 15) Measurement of 10 m snow temperature; 16) Geomorphological observation of the ice surface; 17) Geomorphological survey of ice mounds at 69°40'S, 44°12'E; 18) Traverse survey from Syowa Station to Mizuho Camp; 19) Collection of meteorites in the vicinity of the Yamato Mountains. departmental bulletin paper